Dinamika Budaya Megibung Dalam Kehidupan Keagamaan Dan Sosial Di Desa Dukuh Karangasem-Bali - Putra, I Wayan Sunampan; Heriyanti, Komang (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This research is one of the studies that starts from the problem of the dynamics of megibung culture in the life of society. The purpose of this study is to analyze the occurrence of megibung cultural dynamics in the religious and socio-cultural life of society. In the research process using qualitative research types. The process of collecting data with observation, interviews, and document studies. The collected data is then analyzed so that the results are obtained that there are factors that cause megibung cultural dynamics such as ideological factors, sociological factors, and economic factors of society. The implications that occur are that they have implications for religious life, then also have implications for socio-cultural life. The dynamics that occur certainly have an impact on the religious and cultural life of society.